2022
DOI: 10.3389/fimmu.2022.921483
|View full text |Cite|
|
Sign up to set email alerts
|

Antimicrobial Resistance in the COVID-19 Landscape: Is There an Opportunity for Anti-Infective Antibodies and Antimicrobial Peptides?

Abstract: Although COVID-19 has captured most of the public health attention, antimicrobial resistance (AMR) has not disappeared. To prevent the escape of resistant microorganisms in animals or environmental reservoirs a “one health approach” is desirable. In this context of COVID-19, AMR has probably been affected by the inappropriate or over-use of antibiotics. The increased use of antimicrobials and biocides for disinfection may have enhanced the prevalence of AMR. Antibiotics have been used empirically in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 128 publications
0
19
0
Order By: Relevance
“…It can develop either spontaneously or as a result of other factors. After an intensive surgical procedure, such as treatment for endometrial cancer, a patient may become colonized with various types of bacteria, and may need to stay in the hospital longer 221 . It is possible that the usage of antimicrobial bandages might improve several wound healing factors 222,223 …”
Section: Several Applications Of Nano‐biotechnologymentioning
confidence: 99%
“…It can develop either spontaneously or as a result of other factors. After an intensive surgical procedure, such as treatment for endometrial cancer, a patient may become colonized with various types of bacteria, and may need to stay in the hospital longer 221 . It is possible that the usage of antimicrobial bandages might improve several wound healing factors 222,223 …”
Section: Several Applications Of Nano‐biotechnologymentioning
confidence: 99%
“…Antimicrobial resistance (AMR) represents a global threat where microbial pathogens continue to evolve and develop resistance to existing antibiotics, putting the world in another pandemic ( Aljeldah, 2022 ). The extensive use of antibiotics in the treatment of bacterial infections in COVID-19 patients enhanced the prevalence of AMR, which might result in clinical complications and the development of multidrug-resistant microorganisms ( Pérez de la Lastra et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this frame, it has also emerged that not only toxicity but also antimicrobial resistance is a very dangerous effect caused by excessive chemical use ( Singh, 2020 ). In particular, due to the biocidal characteristics of disinfectants, their excessive use is associated with an increase in antimicrobial resistance ( Pérez de la Lastra et al, 2022 ). It is reported that exposure to 0.0004% phenolic disinfectant triclosan increases the risk to develop bacterial resistance and cross-resistance in Staphylococcus aureus and Escherichia coli ( Wesgate et al, 2016 ).…”
Section: Environmental Challengesmentioning
confidence: 99%